Atypical Teratoid/Rhabdoid Tumor Originated From the Trigeminal Nerve in a Young Male Adult: Case Report and Review of the Literature - Chen, Fuxiang; Mei, Wenzhong; Lu, Wen; Zeng, Tiefa; Kang, Dezhi; Wu, Xiyue; You, Honghai (Frontiers in Neurology, 2020)
Atypical teratoid/rhabdoid tumor (AT/RT) is a highly malignant central nervous system neoplasm predominantly found in children under the age of 3 years, and is extremely rare in adults. There is no specific clinical presentations or radiological features in reported cases of AT/RT. Diagnosis of brain AT/RT is mainly dependent on the classical pathological characteristics. We report a rare case of AT/RT arising from the trigeminal nerve and leading to progressively multiple cranial nerve palsies in a 25-year-old male patient. Microsurgical resection of the tumor has been performed and confirmed the diagnosis by postoperative pathology. To our knowledge, this is the second case of adult-onset AT/RT originating from the trigeminal nerve.